Women, public life and democracy : changing Commonwealth parliamentary perspectives - Lovenduski, Joni; Campbell, Rosie, 1967-; Sampson-Jacent, Jacqui (Commonwealth Parliamentary Association in Association, with Pluto Press, 2002)
A practical guide to the growing influence of women on parliamentary legislation across the Commonwealth.
Preface -- Women, public life and democracy -- Introduction -- Setting out the terms / by Prof. Joni Lovenduski -- The Role of Parliamentarians -- Representation without the incumbency barrier: the example of Scotland -- Waving goodbye to dinosaurs: the Northern Ireland Women's Coalition -- Making Parliamentarians listen to women voters and getting women elected -- The Beijing process -- Gender mainstreaming Affirmative Action: help or hindrance? -- Education and sex equality equalising access to care and services -- The Nordic model: The Example of Finland Equality Policy. The example of Malaysia : the implementation of equal rights legislation / by Hon. Gillian James -- Does size matter? sex equality in small states -- How can NGOs lobby for change? A Users guide / by Georgina Ashworth -- Improving access to credit, technology and business -- Can the media be resexed? / by Jackie Ashley -- Conclusions / by Rosie Campbell -- What works and what does not for women in politics? a Commonwealth perspective / by the Commonwealth Parliamentary Association -- Institutional framework for mainstreaming gender in public service personnel management / by the Commonwealth Secretariat Affirmative Action in the Commonwealth Secretariat -- Part 2. Gender-sensitizing Commonwealth Parliaments: report of a CPA Study Group, February-March 2001 / by Mrs Jacqui Sampson-Jacent -- Gender-sensitizing Commonwealth Parliaments: Commonwealth Parliamentary Conference Plenary report, September 2001 -- Report of a Commonwealth Parliamentary Conference Workshop on Gender, September 2001 -- Strategic partnerships for politics in the 21st Century : Report of a Commonwealth Women Parliamentarians Meeting, September 2001 -- Representation of Women in Commonwealth Parliaments and Legislatures.
Keywords: Commonwealth; Women -- Political activity -- Commonwealth countries.; Women's rights -- Commonwealth countries.; Femmes -- Activité politique -- Pays du Commonwealth.; Femmes -- Droits -- Pays du Commonwealth.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; SOCIAL SCIENCE -- Sociology -- General.; Women -- Political activity; Women's rights; Commonwealth countries; Parlamentarismus; Politikerin; Aufsatzsammlung; Gleichberechtigung; Frau; Femmes et politique -- Commonwealth.; Femmes -- Droits -- Commonwealth.